2007
DOI: 10.1007/s00335-007-9049-x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted knockout and lacZ reporter expression of the mouse Tmhs deafness gene and characterization of the hscy-2J mutation

Abstract: The Tmhs gene codes for a tetraspan transmembrane protein that is expressed in hair cell stereocilia. We previously showed that a spontaneous missense mutation of Tmhs underlies deafness and vestibular dysfunction in the hurry-scurry (hscy) mouse. Subsequently, mutations in the human TMHS gene were shown to be responsible for DFNB67, an autosomal recessive nonsyndromic deafness locus. Here we describe a genetically engineered null mutation of the mouse Tmhs gene (Tmhs ( tm1Kjn )) and show that its phenotype is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…We identified a homozygous, unique SNP in that critical region at 2,815,634 on chromosome 11 that causes a premature stop codon at residue 80 of Lhfpl5a (ENSDARG00000045023). The homolog of lhfpl5a, LHFPL5, causes nonsyndromic deafness in humans and the hurry scurry (hscy) mouse, thus making it a strong candidate (Longo-Guess et al, 2005;Shabbir et al, 2006;Longo-Guess et al, 2007). However, we could not validate this mutation by morpholino phenocopy, possibly because lhfpl5a functions at a late stage of development by which time the morpholinos have been degraded.…”
Section: Identification Of Lesions In Lmx1b Jag1b and Cdh23mentioning
confidence: 86%
See 1 more Smart Citation
“…We identified a homozygous, unique SNP in that critical region at 2,815,634 on chromosome 11 that causes a premature stop codon at residue 80 of Lhfpl5a (ENSDARG00000045023). The homolog of lhfpl5a, LHFPL5, causes nonsyndromic deafness in humans and the hurry scurry (hscy) mouse, thus making it a strong candidate (Longo-Guess et al, 2005;Shabbir et al, 2006;Longo-Guess et al, 2007). However, we could not validate this mutation by morpholino phenocopy, possibly because lhfpl5a functions at a late stage of development by which time the morpholinos have been degraded.…”
Section: Identification Of Lesions In Lmx1b Jag1b and Cdh23mentioning
confidence: 86%
“…Alagille syndrome pathology also includes inner ear dysplasia (Koch et al, 2006). In contrast to syndromic phenotypes, autosomal recessive mutations in the human orthologs of both cdh23 and lhfpl5a cause nonsyndromic deafness (Bolz et al, 2001;Bork et al, 2001;Longo-Guess et al, 2005;Shabbir et al, 2006;Longo-Guess et al, 2007). Along with Protocadherin 15, Cdh23 has recently been identified as one of the components of the tip links of hair-cell bundles, where mechanical forces are transduced into electrical potentials (Kazmierczak et al, 2007;Sakaguchi et al, 2009).…”
Section: Research Articlementioning
confidence: 99%
“…Car2-deficient (Car2 Ϫ/Ϫ ) mouse embryos and wild-type (Car2 ϩ/ϩ ) C57BL/6J mice were purchased from Jackson Laboratory (Bar Harbor, ME). The initial coding sequence of the Car2 gene was replaced with a LacZ marker under the direction of the Car2 promoter (25). Heterozygous (Car2 ϩ/Ϫ ) mice were rederived on a C57BL/6 genetic background at the Transgenic Core at the Research Institute of Nationwide Children's Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…These four proteins are Tmc1 (transmembrane channel protein 1), Tmc2 (transmembrane channel protein 2) (Beurg et al, 2014(Beurg et al, , 2015Kawashima et al, 2011;Pan et al, 2013), Tmhs (tetraspan membrane protein of hair cell stereocilia, also know as Lhfpl5) (Beurg et al, 2015;Longo-Guess et al, 2007, 2005Xiong et al, 2012) and Tmie (transmembrane protein of inner ear hair cells) (Karuppasamy et al, 2012;Mitchem et al, 2002;Park et al, 2013; Su CD3-specific sequence (encoded by exon 39) is indicated in yellow, and the sequence encoded by exon 37 is indicated in green. Protein sequences encoded by phases other than the conventional phase are indicated in gray.…”
Section: Q4mentioning
confidence: 98%